Temperature-Dependent Electrochemical Stability Window of Bis(trifluoromethanesulfonyl)imide and Bis(fluorosulfonyl)imide Anion Based Ionic Liquids - Lethesh, Kallidanthiyil Chellappan; Bahaa, Ahmed; Abdullah, Mariam; Bamgbopa, Musbaudeen O.; Susantyoko, Rahmat Agung (Frontiers in Chemistry, 2022)
The electrochemical stability of 22 commercially available hydrophobic ionic liquids was measured at different temperatures (288.15, 298.15, 313.15, 333.15 and 358.15 K), to systematically investigate ionic liquids towards electrolytes for supercapacitors in harsh weather conditions. Bis(trifluoromethanesulfonyl)imide and bis(fluorosulfonyl)imide anions in combination with 1-Butyl-1-methylpyrrolidinium, 1-Ethyl-3-methylimidazolium, N-Ethyl-N, N-dimethyl-N(2methoxyethyl)ammonium, 1-Methyl-1-(2-methoxyethyl)pyrrolidinium, N-Pentyl-N-methylpyrrolidinium, N, N-Diethyl-N-methyl-N-propylammonium, N, N-Dimethyl-N-ethyl-N-benzyl ammonium, N, N-Dimethyl-N-Ethyl-N-phenylethylammonium, N-Butyl-N-methylpiperidinium, 1-Methyl-1-propylpiperidinium, N-Tributyl-N-methylammonium, N-Trimethyl-N-butylammonium, N-Trimethyl-N-butylammonium, N-Trimethyl-N-propylammonium, N-Propyl-N-methylpyrrolidinium cations were selected for the study. Linear regression with a numerical model was used in combination with voltammetry experiments to deduce the temperature sensitivity of both anodic and cathodic potential limits (defining the electrochemical stability window), in addition to extrapolating results to 283.15 and 363.15 K. We evaluated the influence of the cations, anions, and the presence of functional groups on the observed electrochemical stability window which ranged from 4.1 to 6.1 V.